2019
DOI: 10.1016/j.ijpharm.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic delivery of functional siRNA using pH-Responsive nanoscale hydrogels

Abstract: The progress of short interfering RNA (siRNA) technologies has unlocked the development of novel alternatives for the treatment of a myriad of diseases, including viral infections, autoimmune disorders, or cancer. Nevertheless, the clinical use of these therapies faces significant challenges, mainly overcoming the charged and large nature of these molecules to effectively enter the cell. In this work, we developed a cationic polymer nanoparticle system that is able to load siRNA due to electrostatic interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In each interval, a hydrodynamic diameter and count rate were recorded. Because count rate trends with the number of particles in solution ( 37 ), the count rate at a given time, normalized to the initial count rate, provided a measure of the degree of degradation.…”
Section: Methodsmentioning
confidence: 99%
“…In each interval, a hydrodynamic diameter and count rate were recorded. Because count rate trends with the number of particles in solution ( 37 ), the count rate at a given time, normalized to the initial count rate, provided a measure of the degree of degradation.…”
Section: Methodsmentioning
confidence: 99%
“…[35,42] For example, Liechty et al recently demonstrated that incorporating hydrophobic moieties into a hydrogel network could significantly alter its cell membrane disruption properties. [52] This discrepancy could explain why no clear linear correlation between the DS value and FD10 delivery efficiency was observed.…”
Section: Scrutinizing Nanogel Properties For Improved Cytosolic Cargo Deliverymentioning
confidence: 99%
“…With respect to size, nanoscale materials are ideally suited for RNA delivery because they can protect RNA from degradation, extend circulation half‐life, facilitate cellular entry, and increase therapeutic index . Indeed, various nanoparticle (NP) delivery systems have shown considerable promise for the delivery of plasmid DNAs, antisense oligonucleotides, small interfering RNAs (siRNAs), and miRNAs to diseased cells in vitro and in vivo . When considering size as a design parameter for miRNA mimic delivery vehicles, it is important to note that NPs with diameters less than ∌5 nm rapidly undergo renal clearance upon intravenous administration and those with diameters greater than ~200 nm exhibit splenic filtration due to the 200–500 nm size range of interendothelial cell slits .…”
Section: Design Parameters For Mirna Mimic Delivery Vehiclesmentioning
confidence: 99%
“…Polymer materials have been widely explored as tools to carry therapeutic cargo (e.g., small molecules, peptides, proteins, DNAs, siRNAs, and miRNAs) to specific tissues/cells to intervene in disease . The types of polymers that have been incorporated into delivery vehicles include poly(lactic‐ co ‐glycolic acid) (PLGA), PEG, poly‐ L ‐lysine (PLL), poly‐ L ‐arginine (PLA), PEI, and more.…”
Section: Polymer Nanocarriers For Mirna Deliverymentioning
confidence: 99%